Desenvolvimento e caracterização reológica de oleogéis mistos contendo ésteres de sacarose - Cruz, Ana Nathália Fernandes da (Universidade Federal de São Carlos, 2020)
The structuring of liquid oils has become an attractive area of research in recent years, especially due to pressures to reduce saturated fat intake and eliminate trans fats from our diets. However, the replacement of fats rich in saturated fatty acids with liquid oil can lead to major changes in the quality characteristics of processed foods. Recents strategies for providing saturated fat functionality to liquid oils include the addition of lipid structuring agents to the oil, leading to its gelation. The objective of this Project was to study the characteristics of formation of oleogels from the combination of lipid structuring agents such as monoacylglycerol (MAG), soy lecithin (LEC) and sucrose fatty ester (ES) in high oleic sunflower oil (HOSO), using for this, a planning of mixtures of the extreme vertex type. The obtained oleogels were analyzed for their mechanical properties and rheological behavior. The mechanical properties were analyzed using the direct extrusion method (Backward Extrusion), and when statistically treating the data, the regression analysis indicated that the best fit for the samples was obtained with the linear model. The test reponses indicated that lecithin had a significant influence (p < 0,05) oin the texture properties of the oleogels that contain it in ternary interactions (ES + LEC + MAG). The rheological behavior was accomplished in a rotational rheometer, where flow curves and apparent viscosity were obtained. The adjustments to the Power Law model were better for all samples, where they showed a pseudoplastic behavior (n < 1). Apparently, the samples showed similar behavior, in the descending ramp at the beginning of the shear at high deformation rates, they were more structured, however, as the shear continued with the decrease in the deformation rate, they tended to Newtonian behavior. However, when increasing the deformation rate in the ascending ramp (ramp 2), they showed pseudoplastic behavior and thixotropy, which was confirmed by the apparent viscosity curves, indicating change and loss of structure. The rheological parameters were consistent with the texture data and showed the effect of the sample formulation. It was possible to conclude that the samples with ternary interactions with higher levels of ES made the materials a little more resistant, minimizing changes in apparent viscosity, and the most structured sample was the E5 that had intermediate LEC values. The results obtained may allow its application in food formulations when subjected to conditions of industrial processes that require lower deformation rates (100 a 103) such as extrusion, mixing, pumping and/or sedimentation, however further studies of formulation to increase the resistance are necessary.
Development and rheological characterization of mixed oleogels containing sucarose esters
Keywords: oleogel, óleo de girassol alto oleico, estruturantes, éster graxo de sacarose, propriedades mecânicas, comportamento reológico; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS